2012
DOI: 10.1158/1078-0432.ccr-11-2696
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Tumor PIK3CA Status in Metastatic Breast Cancer Using Peripheral Blood

Abstract: Purpose We sought to evaluate the feasibility of detecting PIK3CA mutations in circulating tumor DNA (ctDNA) from plasma of patients with metastatic breast cancer using a novel technique called BEAMing. Experimental Design In a retrospective analysis, 49 tumor and temporally matched plasma samples from patients with breast cancer were screened for PIK3CA mutations by BEAMing. We then prospectively screened the ctDNA of 60 patients with metastatic breast cancer for PIK3CA mutations by BEAMing and compared the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
194
0
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 295 publications
(216 citation statements)
references
References 34 publications
14
194
0
3
Order By: Relevance
“…previously published studies despite the fact that we used a very low amount of cfDNA, which in most cases was isolated from much less than 0.5 ml of plasma [17][18][19][20][21]. Collectively, there is increasing evidence that the mutation analysis results for cfDNA are highly concordant with those for archival tumor tissue for concordantly, but not discordantly, collected samples, which may be explained by tumor biology, including heterogeneity and evolution over time [10,21].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…previously published studies despite the fact that we used a very low amount of cfDNA, which in most cases was isolated from much less than 0.5 ml of plasma [17][18][19][20][21]. Collectively, there is increasing evidence that the mutation analysis results for cfDNA are highly concordant with those for archival tumor tissue for concordantly, but not discordantly, collected samples, which may be explained by tumor biology, including heterogeneity and evolution over time [10,21].…”
Section: Discussionmentioning
confidence: 90%
“…A certain level of discordance can be anticipated if the tumor tissue and plasma are not obtained at the same time. Higgins et al [17] found 100% agreement between PIK3CA mutation testing of plasma cfDNA with BEAMing PCR and tumor tissue collected in a cohort of patients with advanced breast cancer and simultaneous collection. However, the concordance between the methods decreased to 79% in a cohort of patients whose tumor and plasma cfDNA samples were obtained at different times, which is consistent with Figure 2.…”
Section: Discussionmentioning
confidence: 99%
“…In order to investigate PIK3CA mutations which concentrate within only few hot spots this is feasible, since up to 10 SNPs can be screened at once. As aforementioned the sensitivity of the SNaPshot methodology was reported to be approximately 5% (Hurst et al, 2009); an even higher detection rate (up to 0.01%) might be achieved by the recently published BEAMing technology (Beads, Emulsification, Amplification, and Magnetics; Higgins et al, 2012) which is also based on PCR amplification of hot spot regions. However, neither the SNaPshot nor the BEAMing technique allows for the discovery of unknown mutations.…”
Section: Discussionmentioning
confidence: 90%
“…On the other hand, mutated proteins observed in cancer, including H1047R, E545K and E542K, activate AKT signaling to oncogenic growth of cancer cells. Previous study has reported that PIK3CA mutations were detected in ctDNA from patients with metastatic breast cancer using digital PCR [8]. The levels of the mutated PIK3CA in ctDNA showed a larger dynamic range and more significant correlation with the tumor burden than other known tumor markers in metastatic breast cancer [9].…”
Section: Introductionmentioning
confidence: 90%